A New Recyclable Yttrium-Catalyzed Domino Three-Component Approach to the Synthesis of 3-Methyl-4 arylmethylene Isoxazol-5(4H)-ones - Ilaamirthamani, Simsonrubarathinam; Kumarraja, Mayilvasagam (Letters in Organic Chemistry, 2025)
In this study, a domino multicomponent strategy was followed for the cyclo condensation reaction of aldehydes with β-ketoesters and hydroxylamine hydrochloride to produce a variety of 3,4-disubstituted isoxazol-5(4H)-ones using a novel Yttrium (III)-MMZ catalyst. Aprotic polar solvents and hard Lewis acid metal ions were found to greatly influence the reaction. In this study, the effect of the Y3+ in the MMZ framework and the nature of substrates and their positions in determining the yield of products were also described, along with a supporting mechanism. The structural morphology of Y3+-MMZ was characterized by the electron microscopic technique, and the loading level of Y3+ ions was determined by EDAX analysis. Most of the experiments did not require further purification by column chromatography. The present catalytic method offers several other advantages over the other reported methods, such as easy preparation, recyclization of the catalyst (up to 3 times), mild reaction conditions, shorter reaction time, and ease of work-up on recovering the products.
Keywords: aldehydes